Iterative Learning Control with Input Saturation. Issue 29 (2019) - Pakshin, Pavel; Emelianova, Julia; Rogers, Eric; Galkowski, Krzysztof
Abstract: The paper considers iterative learning control for differential and discrete linear systems with control input saturation. A new design is developed based on the use of a full state observer in combination with the method of vector Lyapunov functions and dissipativity theory for repetitive processes. An example demonstrating the features and advantages of the new design is given.